Stimulation of Mononuclear Cells Through Toll-Like Receptor 9 Induces Release of Microvesicles Expressing Double-Stranded DNA and Galectin 3-Binding Protein in an Interferon-α-Dependent Manner - Rasmussen, Niclas Stefan; Nielsen, Christoffer Tandrup; Jacobsen, Søren; Nielsen, Claus Henrik (Frontiers in Immunology, 2019)
Background: Microvesicles (MVs) expressing the type 1 interferon (IFN)-inducible protein galectin-3 binding protein (G3BP) may play a pathogenic role in systemic lupus erythematosus (SLE). Co-expression of double-stranded DNA (dsDNA) on such MVs may render them immunogenic and targets for anti-dsDNA antibodies. Little is known about the mechanisms underlying generation of this MV population. In this study, we investigated how Toll-like receptors (TLRs), IFN-α, and T cells are involved in this process in healthy subjects. Methods: Peripheral blood mononuclear cells (PBMCs) isolated from 12 healthy donors were stimulated in-vitro for 24 h with a series of TLR-agonists or the T cell activating antibody OKT3 or were subjected to apoptosis by incubation with staurosporine. MVs in the supernatants were subsequently isolated by differential centrifugation and were quantified and characterized with respect to expression of G3BP and dsDNA by flow cytometry. Results: Stimulation of PBMCs with the TLR9-agonist and strong IFN-α inducer ODN2395 significantly increased the release of MVs expressing G3BP. The production of MVs with this phenotype was markedly enhanced by co-stimulation of T cells. Furthermore, dependency on IFN-α in the generation of G3BP-expressing MVs was indicated by a marked reduction following addition of the IFN-α inhibitor IFN alpha-IFNAR-IN-1 hydrochloride. Conclusion: Release of G3BP-expressing MVs from healthy donor PBMCs is induced by stimulation of TLR9 in an IFN-α-dependent manner and is enhanced by co-stimulation of T cells.